Radiographic features of Wu et al. type A2 congenital thumb duplication and implications for management: new subtypes and surgical strategies - JianPing Wu; ShiJie Liao; YuQuan Li; FuLong Xu; Hai Zhao; ChenYang Li; YanHan Liu; XinWang Zhi; HongHong Lin; ZheHui Tu; LiLi Shu; JingChun Li; et al. (Frontiers in Pediatrics)
ObjectiveThis study aimed to assess the radiographic features of patients diagnosed with congenital thumb duplication (CTD) type A2 based on the Wu et al. classification, describe the different subtypes of duplications and propose a classification system that permits identifying various surgical strategies.MethodsWe evaluated 665 patients (680 thumbs) diagnosed with type A2 CTDs by examining the alignment of the interphalangeal (IP) and metacarpophalangeal (MP) joints of the primary thumb on posteroanterior (PA) radiographs. The classification system has four types: Type I (no deviation); Type II (ulnar deviation); Type III (hypertrophic epiphysis); and Type IV (convergent). Types I-IV were compared to Hung et al.'s system Type A-D (Hypoplastic, Ulnar Deviation, Divergent, and Convergent).ResultsOf the 680 fingers, 436 (64.1%) were determined to be Wassel type IV while 244 (35.9%) were classified as Wassel type VII. All of the 436 fingers could be categorized according to the subtypes of the Hung et al. system; in particular, 369 (84.6%) were identified as type B, 52 (11.9%) as type D, and 15 cases (3.4%) as type C. The proposed classification system worked effectively for all CTDs (n = 680). 494 cases were classified as type II (72.6%), while 75 cases were classified as type I (11.0%). The remaining 111 cases were further classified as either type IV (9.3%) or type III (7.1%). The Wu et al. systems showed excellent intra-rater (0.881) and inter-rater (0.873) reliability compared to the Hung et al. systems (0.842 and 0.823, respectively).ConclusionsThe proposed radiographic pathoanatomical system has the potential to improve communication and guide optimal procedure selection for different subtypes of CTD depending on the attachment of the extra digit to the main thumb and the alignment of the interphalangeal and metacarpophalangeal joints of the primary thumb (Wu et al. type A2).Level of evidenceIII